Nursing Students Attitudes toward Virtual Learning and its Relationship with Learning Style - Mahboubeh Vatan-Parast; Zahra Royani; Hossein Ghasemi (Kerman University of Medical Sciences, 2015)
Background & Objective: Today the concept of virtual education has gained much attention as distance learning and has provided learning opportunities outside the borders of a country or state for everyone The consideration of the success of virtual training is impossible without the consideration of individuals viewpoints toward it Despite this fact less attention has been paid to students attitudes in the published studies This study investigates the students attitudes toward virtual education and its relationship with learning styles Methods: In this correlationdescriptive study 114 bachelors and masters students of Razi School of Nursing and Midwifery of Kerman Iran in 2013 were selected based on census sampling method Data were collected using demographic questionnaire the researchermade questionnaire of attitude toward virtual learning and the Gaziano Learning Styles Questionnaire Data were analyzed using descriptive statistics (mean and standard error) independent ttest ANOVA Pearson correlation and linear regression in SPSS software All Pvalues of ;le 005 were considered significant Results: The mean score of nursing students attitude toward virtual learning was 330 ± 034 The highest frequency among learning styles used by students was related to visual (50%) auditory (272%) and kinetic styles (228%) In the regression analysis visual style (P = 0009 ;beta = 027) and auditory style (P = 0008 ;beta = 017) had a significant relationship with attitudes of nursing students toward virtual education Conclusion: Students had positive attitudes toward virtual learning Moreover attitudes toward virtual education differed among people with different learning styles Therefore the consideration of individual needs and different learning styles of learners is essential in virtual education